Pertumbuhan dan Kandungan Minyak Atsiri Tanaman Selasih (Ocimum basilicum L.) pada Naungan dan Dosis Pupuk Fosfat yang Berbeda - Sholehah, Diana Nurus; ,, Suhartono; Lesmana, dan Angga (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2018)
Basil (Ocimum basilicum L.) is a plant that has great potency  to be developed. Almost all parts of the plant can be utilized. This study aimed to determine the effect of shade and phosphate fertilizer on growth and essential oil content in  basil. This research was conducted at the experimental field of Agrotechnology Departement, Faculty of Agriculture, University of Trunojoyo Madura, during January-April 2015. The research was arranged in a split plot design with 3 replications. Main plot was shading i.e., without shading  and 25% shading. The subplots were phosphate fertilizer rate, i.e., 0, 1.5, 3.0, and 4.5 g SP36 per plant that was planted in polybags. The results showed that plants treated with 25% of shading and applied with phosphate 3 g per plant had the highest total dry weight, production of essential oil and eugenol. Shading of 25% give the best results on plant height, leaf area and total fresh weight of the plant. Application of phosphate fertilizer 3 g per plant give  the highest content of chlorophyll (chlorophyll b and total chlorophyll), while the highest essential oil and eugenol content of leaves is obtained from application of phosphate fertilizer 3 and 4.5 g per plant. Shading  and phosphate fertilizer application did not affect leaf  number.